2014
DOI: 10.1021/la500234r
|View full text |Cite
|
Sign up to set email alerts
|

Bubble Formation at a Gas-Evolving Microelectrode

Abstract: The electrolytic production of gas bubbles involves three steps--nucleation, growth, and detachment. Here the growth of hydrogen bubbles and their detachment from a platinum microelectrode of diameter 125 μm are studied using high-speed photography and overpotential frequency spectrum (noise) analysis. The periodic release of large <800 μm bubbles--gas oscillator behavior--was often observed, with a corresponding periodic oscillation of the overpotential which is reflected as a main peak and a series of harmon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
145
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(162 citation statements)
references
References 56 publications
8
145
2
1
Order By: Relevance
“…This is due to a reduction of the active electrode area, leading to a change of the current distribution and an increase of the resistance. 28 At about 60% of the entire residence time of the bubble at the electrode, the absolute value of the current starts to increase again while the bubble continues to grow until it is able to detach from the electrode and the evolution process starts all over again. It was suggested that the increase of the current in the final stages of the bubble growth is associated with a translation of the bubble along the electrode surface 27 or small electrolyte channels 28 forming in the interface between the bubble and the electrode surface, thus increasing the active electrode area.…”
Section: Resultsmentioning
confidence: 99%
“…This is due to a reduction of the active electrode area, leading to a change of the current distribution and an increase of the resistance. 28 At about 60% of the entire residence time of the bubble at the electrode, the absolute value of the current starts to increase again while the bubble continues to grow until it is able to detach from the electrode and the evolution process starts all over again. It was suggested that the increase of the current in the final stages of the bubble growth is associated with a translation of the bubble along the electrode surface 27 or small electrolyte channels 28 forming in the interface between the bubble and the electrode surface, thus increasing the active electrode area.…”
Section: Resultsmentioning
confidence: 99%
“…Electrochemical noise analysis provides a frequency spectrum, [22] and it suggests that bubbles grow by coalescence with much smaller ones, [20,21,23] something that can be observed directly, together with microbubble growth and release, using high-speed photography. [21,24] Magnetic field does modify the bubbling regime, but surface tension appears to be the critical factor.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…[34][35][36] In addition to influencing bubble behavior, SLS can also be absorbed on the cathode surface. Gomez et al 37 found that SLS helped to render Zn electrodeposits more crystalline than other additives due to the larger overpotential evident in changes of voltammetry curves attributed to SLS adsorption.…”
Section: D844mentioning
confidence: 99%